Assessment of The Impact of Apremilast on Levels of IL-17, IL-23, and Lipids in Obese Psoriatic Patient - Haitham M. Saad; Adil A. Noaimi; Halla Gh. Mahmood (مجلة كلية الطب)
Background: Psoriasis is an immune-mediated inflammatory disease with unknown aetiology that may be associated with the defect in proliferation and differentiation of the keratinocytes related to inflammatory cell infiltration. According to published reports, it is universal in occurrence; its prevalence in different populations varies from 0.1% to 11.8%. Receiving Apremilast resulted in a strong reduction in interleukin 17 and interleukin 23, as well as reduced expression of other inflammatory cytokines and improvement of psoriatic lesions.